Acute myocardial infarction treatment delay in South Asia: a systematic review and meta-analysis - Deepthi Ramamurthy (21378310) (2025)
Acute Myocardial Infarction (AMI) necessitates timely treatment to improve outcomes. Identifying treatment delays across different South Asian countries can aid in formulating policies to reduce these delays. Objectives: To estimate the average treatment delay in AMI patients in South Asia and identify contributing factors. Using the CoCoPop framework (Condition, Context, Population), studies were reviewed on AMI treatment delays in South Asia from 2000 to 2022. Databases searched included PubMed Central, Embase and Google Scholar. Eligible studies were cross-sectional and analytical that reported exact delay times, excluding knowledge, attitude, practice studies, narrative reviews, and case reports. The search yielded 2954 records, with 42 studies meeting the inclusion criteria. The pooled median prehospital delay was 531 minutes (95% CI: 366–769 minutes). The pooled mean door-to-ECG time was 9.18 minutes (95% CI: 2.52–15.84 minutes). The door-to-needle and door to balloon time among STEMI patients were 37.95 (95% CI: 30.11–45.78 minutes) minutes and 62.92 minutes (95% CI: 45.28–80.56 minutes), respectively with significant heterogeneity. Factors associated with delays included old age, female gender, low literacy, ignorance, financial constraints, and rural location. Significant treatment delays for AMI patients in South Asia are identified, with socio-economic and logistical barriers contributing to these delays. Acute Myocardial Infarction (AMI), also known as heart attack, needs timely treatment to save lives and improve recovery. Identifying treatment delays in South Asia guides policies to effectively reduce such delays. Studies published between 2000 and 2022 from countries in South Asia were reviewed. It was observed that patients had delays of an average of 531 minutes (nearly 9 hours) to reach the hospital after symptoms began. Once at the hospital, it took around 9 minutes for patients to get an ECG. For patients with a serious heart artery blockage (STEMI) the average time taken from reaching the hospital to starting medicine to break the clot (medicine given through a drip to open blocked arteries) was about 38 minutes. On average, the time taken to reach and start treatment with a heart balloon procedure was about 63 minutes. These times varied widely between studies. Several factors caused delays in treatment, including older age, being female, low education levels, not knowing heart attack symptoms, financial problems, and living in rural areas. This study shows that many people in South Asia experience long delays before getting treatment for heart attacks. Reducing these delays through public awareness, improved transport, and hospital readiness could help save more lives.